2023
DOI: 10.3389/fnut.2023.1147869
|View full text |Cite
|
Sign up to set email alerts
|

Association between composite dietary antioxidant index and handgrip strength in American adults: Data from National Health and Nutrition Examination Survey (NHANES, 2011-2014)

Abstract: BackgroundThe Composite Dietary Antioxidant Index (CDAI), a composite score of multiple dietary antioxidants (including vitamin A, C, and E, selenium, zinc, and carotenoids), represents an individual’s comprehensive dietary antioxidant intake profile. CDAI was developed based on its combined effect on pro-inflammatory markers Tumor Necrosis Factor-α (TNF-α) and anti-inflammatory effects of Interleukin-1β (IL-1β), which are associated with many health outcomes, including depression, all-cause mortality, colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…Lewis et al examined the relationship between dietary and circulating vitamin C with skeletal muscle mass, and found a positive correlation between vitamin C with skeletal muscle mass ( 39 ). In addition, from a study analyzing the association between the NHANES cohort’s dietary antioxidant and grip strength, vitamin E intake was found to be positively associated with grip strength in men ( 40 ). In contrast, a study conducted in Switzerland demonstrated that the supplementation of vitamins C and E neither improved nor prevented low grip strength over a five years ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lewis et al examined the relationship between dietary and circulating vitamin C with skeletal muscle mass, and found a positive correlation between vitamin C with skeletal muscle mass ( 39 ). In addition, from a study analyzing the association between the NHANES cohort’s dietary antioxidant and grip strength, vitamin E intake was found to be positively associated with grip strength in men ( 40 ). In contrast, a study conducted in Switzerland demonstrated that the supplementation of vitamins C and E neither improved nor prevented low grip strength over a five years ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained the mean intake of vitamin A, vitamin C, vitamin E, zinc, selenium, and carotenoids from the CDAI (excluding intake from dietary supplements, medications, or plain drinking water). The CDAI was derived according to the validated method from previous studies ( Wu et al, 2023a , Yu et al, 2022 ), which is to subtract the mean intake of each antioxidant from its intake, normalize by dividing by the standard deviation, and then combine all the figures. The CDAI was calculated as follows (where x represents the intake of individual dietary antioxidants, mean represents the average intake of each component, and SD represents the standard deviation of the mean): …”
Section: Methodsmentioning
confidence: 99%
“…Smoking status was divided into three categories as follows: never (<100 cigarettes in a lifetime), former (>100 cigarettes in a lifetime but no longer smoke), and current (>100 cigarettes in a lifetime and smoke at times or daily). 16 Drinking status was categorized as (a) never drinking, (b) former drinking (having drunk before and not drinking in the last 12 months), (c) mild alcohol user (<2 drinks per day for females, <3 drinks per day for males, or excessive drinking <2 days per month), (d) current moderate drinking (≥2 drinks per day for females, ≥3 drinks per day for males, or excessive drinking ≥2 days per month), and (e) current heavy drinking (≥3 drinks per day for females, ≥4 drinks per day for males, or excessive drinking more than 5 days per month). 17 Asthma and chronic obstructive pulmonary disease (COPD) were diagnosed through a combination of patient self-report, medical history, medication use, and age.…”
Section: Other Variable Definitionmentioning
confidence: 99%